Alteration of growth performance, glycolipid metabolism, and bone characteristics of broiler chickens in response to different inclusion levels of dietary wheat - Yilu Wang; Leilei Wang; Xuemeng Si; Yanqun Huang; Huaiyong Zhang; Wen Chen (Animal Bioscience)
Objective The aim of this study was to evaluate the effects of different levels of wheat inclusion on growth performance, glycolipid metabolism, and tibial properties of broiler chickens. Methods A total of 480 1-d-old male broiler chickens were initially fed identical starter diets until d 10. Subsequently, they were divided into 3 treatments consisting of 8 replicates with 20 birds per replicate, i.e., i) low-level wheat addition group, with wheat ratios of 15% and 25% during the grower and finisher periods, respectively; ii) medium-level wheat inclusion group, incorporating 30% and 40% wheat in the grower and finisher diets, respectively; and iii) high-level wheat addition group, containing 55.8% and 62.4% wheat in the grower and finisher diets, until d 39. Results When compared to the low- and medium-level wheat diet, the high-level wheat inclusion in the diet increased feed intake and reduced the feed conversion ratio (both p<0.01), which was accompanied by a longer jejunum (p = 0.031). Meanwhile, the high-level addition of wheat displayed a decreased abundance of Ruminococcin, Bacteroidetes, and Lactobacillus than the low-wheat group. With the increase of the proportion of wheat treatment, the contents of cholesterol, triglyceride, and high-density lipoprotein cholesterol were elevated in serum, whereas the concentration of serum C-terminal cross-linked telopeptide of type I collagen, a bone resorption marker, was decreased. In addition, the diet with medium and high levels of wheat improved the yield load of tibia, along with comparable bone dimension and weight. Conclusion The medium- and high-level wheat additions increased serum glycolipid deposition and enhanced tibial mechanical properties, whereas the high-level wheat diet compromised the growth performance of broiler chickens, which might be associated with the alteration of gut microbiota.